Measuring Health Inequality with Categorical Data: Some Regional Patterns - Joan Costa-i-Font; Frank Cowell (Center for Economic Studies and ifo Institute (CESifo), 2013)
Much of the theoretical literature on inequality assumes that the equalisand is a cardinal variable like income or wealth. However, health status is generally measured as a categorical variable expressing a qualitative order. Traditional solutions involve reclassifying the variable by means of qualitative models and relying on inequality measures that are mean independent. We argue that the way status is conceptualized has important theoretical implications for measurement as well as for policy analysis. We also bring to the data a recently proposed approach to measuring self-reported health inequality that meets both rigorous and practical considerations. We draw upon the World Health Survey data to examine alternative pragmatic methods for making health inequality comparisons. Findings suggest significant differences in health inequality measurement and that regional and country patterns of inequality orderings do not coincide with any reasonable categorization of countries by health system organization.
Keywords: D63; H23; I18; 330; health inequality; categorical data; health surveys; upward status; downward status